2008
DOI: 10.1523/jneurosci.0182-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation across the Cortical Hierarchy: Low-Level Curve Adaptation Affects High-Level Facial-Expression Judgments

Abstract: Adaptation is ubiquitous in sensory processing. Although sensory processing is hierarchical, with neurons at higher levels exhibiting greater degrees of tuning complexity and invariance than those at lower levels, few experimental or theoretical studies address how adaptation at one hierarchical level affects processing at others. Nevertheless, this issue is critical for understanding cortical coding and computation. Therefore, we examined whether perception of high-level facial expressions can be affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
122
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(149 citation statements)
references
References 59 publications
24
122
3
Order By: Relevance
“…However, the average time from the offset of the second line in a trial to the onset of the first line in the next trial was 6.03 s (including a 2-s intertrial interval), much longer than the 0.5-s interstimulus interval between the two lines within a trial. Given the exponential decay of the tilt aftereffect (40,41), the cross-trial adaptation should be negligible compared with the within-trial adaptation. However, the observed backward aftereffect was as large as the forward aftereffect, ruling out the cross-trial interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the average time from the offset of the second line in a trial to the onset of the first line in the next trial was 6.03 s (including a 2-s intertrial interval), much longer than the 0.5-s interstimulus interval between the two lines within a trial. Given the exponential decay of the tilt aftereffect (40,41), the cross-trial adaptation should be negligible compared with the within-trial adaptation. However, the observed backward aftereffect was as large as the forward aftereffect, ruling out the cross-trial interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Xu, Dayan, Lipkin, and Qian (2008) recently demonstrated that adaptation to concave and convex lines was sufficient to induce aftereffects for perceptions of happiness and sadness when judging the emotional expression of faces, suggesting that adaptation to different mouth shapes can induce aftereffects, at least for perceptions of emotional expressions. However, some models of face perception would suggest that dissociable cognitive routes underpin perceptions of lip speech and emotional expressions (e.g., Bruce & Young, 1986).…”
mentioning
confidence: 99%
“…Little is known about this issue, to the best of our knowledge. Only one very recent study [23] investigated whether low-level curve adaptation affects high-level facial expression judgment. This issue is however crucial to theoretically understand neural coding and computation mechanism, the better understanding for cross-level adaptation interaction will illuminates cross-hierarchy neural response transmission mechanism and implicate how the visual system integrates the complex stimuli from basic visual property.…”
Section: Introductionmentioning
confidence: 99%